2008
DOI: 10.1007/s10964-008-9335-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Violent Media Preference in Cumulative Developmental Risk for Violence and General Aggression

Abstract: The impact of exposure to violence in the media on the long-term development and short-term expression of aggressive behavior has been well documented. However, gaps in this literature remain, and in particular the role of violent media exposure in shaping violent and other serious antisocial behavior has not been investigated. Further, studies of violent media effects typically have not sampled from populations with confirmed histories of violent and/or nonviolent antisocial behavior. In this study, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 49 publications
11
67
3
Order By: Relevance
“…Risk was defined for these analyses as being at or above the 75th percentile (coded 1), or below the 75th percentile (coded 0). This approach is consistent with the procedures established by investigators working in the risk and resilience tradition (Appleyard, Egeland, van Dulmen, & Sroufe, 2005;Boxer et al, 2009). Figure 5 shows the increase in the likelihood of aggression based on the number of risk factors present.…”
Section: Hypothesissupporting
confidence: 79%
“…Risk was defined for these analyses as being at or above the 75th percentile (coded 1), or below the 75th percentile (coded 0). This approach is consistent with the procedures established by investigators working in the risk and resilience tradition (Appleyard, Egeland, van Dulmen, & Sroufe, 2005;Boxer et al, 2009). Figure 5 shows the increase in the likelihood of aggression based on the number of risk factors present.…”
Section: Hypothesissupporting
confidence: 79%
“…Authors such as Boxer et al (2008) highlights the cumulative risk of violent media together with exposure to violence in the community, in the family, in the school and peer groups, academic difficulties, psychopathic tendencies or callousnessunemotionality and psychopathology or related emotional problems. Exposure to entertainment media violence is a risk factor for aggressive behavior, but the presence of this single risk factor is not sufficient to cause children to pick up guns and begin shooting.…”
Section: Cultural Risk and Protection/reliance Factorsmentioning
confidence: 99%
“…Our survey revealed that some children caused pain to dogs unintentionally but others deliberately teased and provoked the dogs by causing them pain as also reported by Akhtar et al (2006). This fact deserves close attention since it may result from overall increasing aggressiveness of children exposed to violent video games connected with lower empathy and stronger proviolence attitudes (Funk 2006), and to media and cartoon violence (Kirsh 2006;Boxer et al 2009). …”
Section: Discussionmentioning
confidence: 65%